Temporal dietary diversity patterns are associated with linear growth but not ponderal growth in young children in rural Vietnam - Duong, C.; Young, M.F.; Nguyen, Phuong Hong; Tran, L.; Patel, S.; Ramakrishnan, U. (Elsevier, 2023)
Background The first 2 y of life mark critical changes in children’s diet from milk-based food to diverse food rich in taste and texture, but few studies in low-resource settings have explored the changes in diet quality during this period.